Suicide among minors - Rohatynska , Nina; Bilosevych, Olena (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article assesses such a negative phenomenon as suicide among minors, its scale in Ukraine and the causes of suicide. Factors leading to juvenile suicide are summarized. It was found that the consequences of suicide by minors are manifested in the form of social and economic losses at various levels.The study is devoted to the question of the causes and motives of suicidal behavior among minors. The author notes that the problem of suicide is a complex and relevant modern socio-pedagogical problem, and the issue of adolescent suicide is gaining special importance. Analyzing the causes and motives of suicide among minors is a difficult task, especially in the context of adolescence. After all, in conflict situations between minors, emotionally immature psychology and self-centered manifestations do not work, such anti-suicidal motives as spiritual values, faith, compassion and love do not work.The need to develop specific methods of suicide prevention among minors in Ukraine is indicated. The author emphasizes the need to develop a system of indicators to assess the phenomenon of suicide in general and child suicide in particular, factors contributing to its spread and the consequences of suicidal behavior of minors.